Herrschaftsumbruch und Historiographie Zeitgeschichtsschreibung als Krisenbewältigung bei Alexander von Telese und Falco von Benevent - Krumm, Markus (Bibliothek des Deutschen Historischen Instituts in Rom, 2021)
The founding of the Kingdom of Sicily was a conflict-laden and eventful process of upheaval, of which we are informed by two historical works by immediate eye witness: the Ystoria by Alexander of Telese and the Chronicon by Falco of Benevento. For the first time, this study consistently analyzes both texts from the perspective and local context of their creation and with regard to their specific pragmatic function.